Efektifitas Berbagai Media Edukasi dalam Meningkatkan Pengetahuan Menopouse (Tinjauan Literatur) - Nikmah, Eva Syafaatun; Aisyaroh, Noveri (Jurnal Midwifery, 2026)
Introduction Knowledge is one of the important factors that determine a woman's readiness in facing menopause. Around 80.9% of women in the premenopause stage worldwide apparently do not have an understanding of the menopause period. One way to broaden knowledge about menopause is through health education using educational media so that the information provided becomes more engaging and easier to understand. Method This article applies a literature review method. Data collection was carried out through the Google Scholar and PubMed databases, covering publications from 2020-2025. Result The analysis of 11 articles found that the media used for education were leaflets, booklets, audiovisuals, videos, brochures, quartet cards, and applications. All of these media were effective in increasing knowledge about menopause. Conclusion Media such as leaflets, booklets, audiovisual materials, videos, brochures, quartet cards, and applications can be used in providing education because they are effective in increasing knowledge about menopause.